Pengaruh Pemberian Pijat Bayi Terhadap Kenaikan Berat Badan Bayi Umur 0-6 Bulan Di BPS Bunda Bukittinggi - Mariza Elvira; Siti Azizah (Jurnal Pembangunan Nagari, 2017)
The massage is not only done when the baby is healthy, but also on sick or fussy babies and infants has become routine care after birth. The purpose of this study was to determine the effect of infant massage on weight gain in infants aged 0-6 months. This type of research is Experimental with Quasy Experiment. The population in this study was 0-6 month-old baby. The sample amounted to 24 people consisting of 12 people who were given infant massage and 12 people were not given infant massage with technique sampling nonprobability. Data was collected using a computerized questionnaire then processed in the univariate and bivariate analyzes. The results obtained infant weight gain on average increased weight infants fed infant massage is 800 gram/month and on average increased weight infants who were not given the baby massage is 233.33 gram/month. Results of statistical test p value = 0.000 visible means no significant difference on average between giving a massage in infants with weight gain in infants aged 0-6 months. The conclusion can be drawn that the baby is gaining weight rapidly increases with doing baby massage, and also advice it to parents to always perform routine infant massage on baby.